2012
DOI: 10.1007/s10453-012-9284-9
|View full text |Cite
|
Sign up to set email alerts
|

NaCl-amendment assay targeting airborne bacteria in tropospheric bioaerosols transported by westerly wind over Noto Peninsula

Abstract: Bioaerosol particles including bacteria, fungi and virus are originated from marine and terrestrial environments. The airborne microorganisms are transported for long-distance through the free troposphere and are thought to influence the downwind ecosystems and human life. However, microbial communities in the free troposphere have not been understood in detail because the direct sampling of microbial cells at high altitude requires sophisticated sampling techniques. In this study, for the investigation of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…However, other studies showed a high proportion of the Bacteroidetes phylum members in bioaerosols in the air above Japan after dust storms in Asia [ 17 , 66 ], as well as in the air above eastern Australia [ 67 ]. The composition of the bacterial microbiome in the upper troposphere above the Noto Peninsula in Japan was quite specific, where it was demonstrated (although using fluorescence in situ hybridization) that 80% of all eubacteria on mineral aerosol particles were represented by Bacillus subtilis belonging to the phylum Firmicutes [ 68 ].…”
Section: Metagenomic Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies showed a high proportion of the Bacteroidetes phylum members in bioaerosols in the air above Japan after dust storms in Asia [ 17 , 66 ], as well as in the air above eastern Australia [ 67 ]. The composition of the bacterial microbiome in the upper troposphere above the Noto Peninsula in Japan was quite specific, where it was demonstrated (although using fluorescence in situ hybridization) that 80% of all eubacteria on mineral aerosol particles were represented by Bacillus subtilis belonging to the phylum Firmicutes [ 68 ].…”
Section: Metagenomic Sequencingmentioning
confidence: 99%
“…Однако другими исследованиями показано высокое содержание представителей Bacteroidetes в биоаэрозоле над Японией после пылевых бурь в Азии [17,66], а также в воздухе над восточной Австралией [67]. Весьма специфичным был состав бактериобиома в высоких слоях тропосферы над полуостровом Ното в Японии, где (правда, методом флуоресцентной гибридизации in situ) показано, что 80% всех эубактерий на минеральных частицах аэрозоля были представлены Bacillus subtilis, относящейся к фирмикутам [68].…”
Section: бактериобиом биоаэрозолейunclassified
“…Unstable compositions at vertical atmospheric height during a polluted sampling day have been reported (Bai et al 2020); thus, the influence of environmental factors on the composition of airborne bacterial communities requires exploration under particular or specific meteorological conditions. In this sense, DNA fingerprint methods such as PCR-DGGE have proven to be particularly useful as a first approach for continuous, cheaper and rapid comparison analysis of airborne bacterial community analyses based on universal 16S rRNA genes (Tanaka et al 2015;Qi et al 2018;Maki et al 2013).…”
Section: Introductionmentioning
confidence: 99%